Patient-reported outcomes in Hodgkin lymphoma trials: a systematic review - Oliva, Esther Natalie; Ionova, Tatyana; Laane, Edward; Csenar, Mario; Schroer, Julia; Behringer, Karolin; Monsef, Ina; Oeser, Annika; Skoetz, Nicole; Salek, Sam (Frontiers in Oncology, 2024)
Background: Lymphoma treatment can lead to long-term consequences such as fatigue, infertility and organ damage. In clinical trials, survival outcomes, clinical response and toxicity are extensively reported while the assessment of treatment on quality of life (QoL) and symptoms is often lacking.Objective: We evaluated the use and frequency of patient-reported outcome (PRO) instruments used in randomized controlled trials (RCTs) for Hodgkin lymphoma (HL) and their consistency of reporting.Methods: MEDLINE, CENTRAL and trial registries for RCTs investigating HL were systematically searched from 01/01/2016 to 31/05/2022. Following trial selection, trial, patient characteristics and outcome data on the use of PRO measures (PROMs) and reporting of PROs using a pre-defined extraction form were extracted. To assess reporting consistency, trial registries, protocols and publications were compared.Results: We identified 4,222 records. Following screening, a total of 317 reports were eligible for fulltext evaluation. One hundred sixty-six reports of 51 ongoing/completed trials were included, of which 41% of trials were completed and 49% were ongoing based on registry entries. Full-text or abstract were available for 33 trials. Seventy percent of trials were conducted in the newly diagnosed disease setting, the majority with advanced HL. In 32 trials with published follow-up data, the median followup was 5.2 years. Eighteen (35%) completed/ongoing trials had mentioned PRO assessment in registry entries, protocol or publications. Twelve trials (67%) had published results and only 6 trials (50%) reported on PROs in part with the exception of 1 trial where PROs were evaluated as secondary/exploratory outcome. The most referenced global PROM was the EORTC-QLQ-C30 (12 studies), the EQ-5D (3 studies) and the FACT-Neurotoxicity (3 studies). FACT-Lymphoma, a diseasespecific PROM for non-HL was mentioned in one ongoing trial. None of the trials referenced the EORTC QLQ-HL27, another disease-specific PROM developed specifically for HL patient's QoL assessment.Discussion: Only one-third of RCTs in HL report PROs as an outcome and only half present the outcome in subsequent publications, showcasing the underreporting of PROs in trials. Disease-specific PROMs are underutilized in the assessment of QoL in HL patients. Guidance on the assessment of PROs is needed to inform on comprehensive outcomes important to patients.